Investigating correlation of soybean (Glycine max (L.) Merill) seed germination with rhizosphere bacterial abundance based on polymerase chain reaction and metagenomic analysis - Timotiwu, Paul B; Setiawan, Wawan A; Manik, Tumiar K; Putri, Adinda N (Agriculture and Natural Resources, 2024)
Importance of the work: Production of soybeans may be enhanced through optimal seed viability. Objectives: To investigate the possibility that good viability soybean seeds in the germination phase will produce abundant bacteria in the rhizosphere. Materials & Methods: Four seed genotypes were analyzed based on germination percentage and radicle emergence. Bacterial DNA was extracted using a Genomic Purification Kit and analyzed using a nanophotometer. The 16S rRNA gene sequencing was amplified using the 63F and 1387 R primers and subsequently visualized using capillary electrophoresis. Bacteria were identified using metagenomic analysis and verified using the nanophotometer and a fluorometer and sequenced using nanopore technology. Results: All soybean seed from the four different genotypes had high values for germination percentage (>96%) and radicle emergence (>85%). However, rhizophore bacterial abundance varied among the four genotypes. The results of DNA extraction showed the highest abundance of rhizosphere bacteria in the Argomulyo genotype, followed by Dena-1, Anjasmoro and Devon-1, respectively. However, based on DNA band visualization, the Anjasmoro genotype had the highest abundance, followed by Argomulyo, Dena-1, and Devon-1, respectively. Rhizosphere bacterial abundance was related more to genotype character. The rhizosphere was mostly dominated by Gram-negative bacteria, indicating that the rhizosphere was occupied by the Proteobacteria phylum, which is common in soil ecosystems. In addition, the study showed that bacteria of the genera Pseudomonas, Lysinibacillus and Clostridium dominated the bacterial community of the soybean rhizosphere. Main finding: Even though soybean seeds from different genotype had good viability, the rhizosphere bacteria might be different in the soil in which the seed have been planted. This finding implied that rhizosphere bacterial abundance might be an indicator for choosing good genotypes in soybean cultivation.